P307 Guideline Development Tool (GDT) – Web-Based Solution For Guideline Developers And Authors Of Systematic Reviews. (15th August 2013) - Brozek, J; Akl, E; Falck-Ytter, Y; Kunstman, P; Meerpohl, J; Mustafa, R; Nowak, A; Oxman, A; Santesso, N; Wiercioch, W; Schünemann, H
Abstract : Background: Guideline developers and other health care decision makers benefit from following a structured process of specifying the health care questions they intend to answer and the outcomes of interest, assessing the confidence in the available evidence, gathering information about the values and preferences of the target population, and presentation of their results and decisions to the target users. Many guideline developers use the GRADE Profiler (GRADEpro) software used to conduct this work. Context: GRADE's approach is currently being further defined in the DECIDE (Developing and Evaluating Communication Strategies to Support Informed Decisions and Practice Based on Evidence) project. Description of Best Practice: The Guideline Development Tool (GDT) is the extension of the GRADE Profiler (GRADEpro) software. The GDT provides an integrated platform-independent web-based solution for health care decision makers offering support for the whole process of making decisions and developing recommendations including question formulation, generation and prioritisation of outcomes, support for teamwork, management of potential conflicts of interest, presentation of results (including the functionality of GRADEpro) and decision support. We tested the software with individual users and in workshops as well as in guideline development processes. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: Following a structured and systematic process, transparency and clarity of presentation facilitates the use of results of systematic reviews and facilitates development, updating and adaptation of evidence-based recommendations and decisions. Storing all information in a uniform, structured, transparent and annotated way also greatly facilitates updating and adaptation of systematic reviews and guidelines.